Fused Hexacyclic Nonfullerene Acceptor with Strong Near‐Infrared Absorption for Semitransparent Organic Solar Cells with 9.77% Efficiency. Issue 31 (13th June 2017) - Wang, Wei; Yan, Cenqi; Lau, Tsz‐Ki; Wang, Jiayu; Liu, Kuan; Fan, Yan; Lu, Xinhui; Zhan, Xiaowei
Abstract : A fused hexacyclic electron acceptor, IHIC, based on strong electron‐donating group dithienocyclopentathieno[3, 2‐ b ]thiophene flanked by strong electron‐withdrawing group 1, 1‐dicyanomethylene‐3‐indanone, is designed, synthesized, and applied in semitransparent organic solar cells (ST‐OSCs). IHIC exhibits strong near‐infrared absorption with extinction coefficients of up to 1.6 × 10 5 m −1 cm −1, a narrow optical bandgap of 1.38 eV, and a high electron mobility of 2.4 × 10 −3 cm 2 V −1 s −1 . The ST‐OSCs based on blends of a narrow‐bandgap polymer donor PTB7‐Th and narrow‐bandgap IHIC acceptor exhibit a champion power conversion efficiency of 9.77% with an average visible transmittance of 36% and excellent device stability; this efficiency is much higher than any single‐junction and tandem ST‐OSCs reported in the literature. Abstract : A fused hexacyclic electron acceptor with strong near‐infrared absorption and high electron mobility is designed, synthesized, and applied in semitransparent organic solar cells, which exhibit a champion efficiency of 9.77% with an average visible transmittance of 36% and excellent device stability.